Quantitative methods for business and economics - Burton, Glyn.; Carrol, George; Wall, Stuart (Harlow : Financial Times Prentice Hall, 2002)
Using real-world examples, the authors clearly demonstrate how quantitative techniques can be applied to business and economics situations. Provides a simple introduction to the mathematical and statistical techniques needed in business. The text is supported by a teacher resource pack that includes a data disk.
Includes bibliographical references and index.
oif 20/02/15; uaj 26/02/15
Loan
Keywords: Economics; Mathematical statistics; Commercial statistics; Industrial management